TORSIONAL CONTROL OF STICK-SLIP OSCILLATIONS IN DRILL-STRING SYSTEM - VIJAYAKUMAR, THESIKAN (IRC, 2017)
The production and extraction of oil and gas, and in addition minerals and geo-thermal sources of energy, depends on the utilization of rotating penetrating framework with drag bits. Drag bits are boring apparatus without moving parts. Penetrating framework with drag bits are known to display torsional vibrations, which may prompt to torsional stick-slip. Torsional stick-slip motions are portrayed by periods in which the boring apparatus arrives at finish stop and periods in which rotational rates of up to a few circumstances the nominal speed is reached. The stick-slip motions diminish the boring proficiency, quicken the wear of drag bits, and may bring about bore string disappointment because of weakness. Torsional control of stick slip oscillation drilling system modelling is a research and results of the selected models which is more complex model known as three mass model. As we know that this model is invented to prove the dynamic relationship between the drill string masses and its amplitude in velocity against time of this drill string. The simulation for the stick slip drilling motion is obtained by solving the equation of motion using MATLAB software.